NILAI-NILAI MANAJEMEN PENDIDIKAN ISLAM DALAM PROSES PENCIPTAAN NABI ADAM AS - Muhammad Arif Syihabuddin (Institut Keislaman Abdullah Faqih Gresik, 2019)
Abstract: This article discusses the value of Islamic education management contained in the process of creating the Prophet Adam as. In Islamic Education management, human resources are one of the main aspects that can determine the sustainability of an organization. If the human resources do not have a strong foundation and guidelines in running the organization, then carrying out the planned activities will be hampered. Therefore, the existing human resources at Islamic Education institutions need to understand the value of management contained in the process of creating the Prophet Adam as. The results of this study explain that the value of management contained in the process of creating the Prophet Adam as including the existence of planning, organizing, actualizing and controlling. These values are hikmah that can be used as guidelines and references in running an organization, and can be used as guidelines in carrying out the duties and roles of humans in life.Keyword: Islamic education management, values,